Bioaugmentation in a Well‐Characterized Fractured Rock DNAPL Source Area. Issue 2 (6th March 2017) - Schaefer, Charles E.; Lavorgna, Graig M.; White, Erin B.; Annable, Michael D.
Abstract: A field demonstration was performed at Edwards Air Force Base to assess bioaugmentation for treatment of a well‐characterized tetrachloroethene (PCE) dense nonaqueous phase liquid (DNAPL) source area in fractured rock. Groundwater recirculation was employed to deliver remedial amendments, including bacteria, to facilitate reductive dechlorination and enhance DNAPL dissolution. An active treatment period of 9 months was followed by a 10‐month posttreatment rebound evaluation. Dechlorination daughter products were observed in both the shallow and deep fracture zones following treatment. In the shallow fracture zone, the calculated DNAPL mass removed was approximately equal to the DNAPL mass estimated using partitioning tracer testing, and no rebound in chlorinated ethenes or ethene was observed during the posttreatment period. A maximum DNAPL dissolution enhancement factor of 5 was observed in the shallow fracture zone. In the deep fracture zone, only approximately 45% of the DNAPL mass—as estimated via partitioning tracer testing—was removed and rebound in the total molar chlorinated ethenes + ethene was observed. The difference in behavior between the shallow and deep fracture zones was attributed to DNAPL architecture and the fracture flow field. Abstract : Article impact statement : The impact of PCE DNAPL architecture on bioaugmentation treatment is assessed in fractured rock.